Upaya meningkatkan kemampuan membaca melalui media kartu gambar pada siswa kelas 1 SD Negeri Cikeusal Kidul 01 tahun pelajaran 2020/2021 - Winda Andriani (Perkumpulan Kualitama Edukatika Indonesia, 2020)
Classroom action research has been carried out to improve and improve students' reading skills through classroom action research using the picture card method. This research was conducted in class I SD Negeri Cikeusal Kidul 01 for the 2020/2021 school year, with a total of 21 students. This study aims to determine whether learning using picture card media can improve students' reading skills. The focus of this study is to determine the level of students' reading skills, student learning outcomes, and teacher performance. The results showed an increase in student learning outcomes were 68.57 and 79.25, respectively. Student learning activities also increased, namely with an average score of 71.03 in the first cycle increasing to 73.91 in the second cycle. It can be concluded that the use of picture card media can improve students' reading skills.